Novel siRNA formulation to effectively knockdown mutant p53 in osteosarcoma - Kundu, Anup K.; Iyer, Swathi V.; Chandra, Sruti; Adhikari, Amit S.; Iwakuma, Tomoo; Mandal, Tarun K. (PLOS ONE, 2017)
Objectives The tumor suppressor p53 plays a crucial role in the development of osteosarcoma. The primary objective of this study is to develop and optimize lipid based nanoparticle formulations that can carry siRNA and effectively silence mutant p53 in 318–1, a murine osteosarcoma cell line. Methods The nanoparticles were composed of a mixture of two lipids (cholesterol and DOTAP) and either PLGA or PLGA-PEG and prepared by using an EmulsiFlex-B3 high pressure homogenizer. A series of studies that include using different nanoparticles, different amount of siRNAs, cell numbers, incubation time, transfection media volume, and storage temperature was performed to optimize the gene silencing efficiency. Key findings Replacement of lipids by PLGA or PLGA-PEG decreased the particle size and overall cytotoxicity. Among all lipid-polymer nanoformulations, nanoparticles with 10% PLGA showed highest mutant p53 knockdown efficiency while maintaining higher cell viability when a nanoparticle to siRNA ratio equal to 6.8:0.66 and 75 nM siRNA was used. With long term storage the mutant p53 knockdown efficiency decreased to a greater extent. Conclusions This study warrants a future evaluation of this formulation for gene silencing efficiency of mutant p53 in tissue culture and animal models for the treatment of osteosarcoma.